2008
DOI: 10.1002/chir.20572
|View full text |Cite
|
Sign up to set email alerts
|

1,3‐bis[N‐sulfonyl‐(1R,2S)‐1,3‐diphenyl‐2‐aminopropanol]benzene: An excellent ligand for titanium‐catalyzed asymmetric AlPh3(THF) additions to aldehydes

Abstract: Asymmetric AlPh(3) (THF) additions to a wide variety of aldehydes catalyzed by a titanium catalyst of 20 mol % 1,3-bis[N-sulfonyl-(1R,2S)-1,3-diphenyl-2-aminopropanol]benzene (1) are reported. The catalytic system works excellently for aromatic aldehydes bearing either an electron-donating or an electron-withdrawing substituent on the aromatic ring to afford secondary diaryl alcohols in excellent isolated yields of >or=95% and excellent enantioselectivities of >or=94% ee. The phenyl addition to cinnamaldehyde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In 2008 Muramatsu and Harada63 introduced a method wherein Grignard reagents (1.2 equiv) could be added to titanium tetraisopropoxide (3 equiv) in the presence of 2 mol % 3-(3,5-Ph 2 -C 6 H 3 )-H 8 -BINOL and aldehydes to provide diarylmethanols with high ee. In a similar vein, Gau and coworkers employed salt-free Ar 3 Al•THF reagents in combination with titanium tetraisopropoxide and either H 8 -BINOL64 or sulfonamide alcohol-based ligands,65 which led to diarylmethanols with high enantioselectivities. These reactions may proceed via an Ar-Ti intermediate 66…”
Section: Introductionmentioning
confidence: 99%
“…In 2008 Muramatsu and Harada63 introduced a method wherein Grignard reagents (1.2 equiv) could be added to titanium tetraisopropoxide (3 equiv) in the presence of 2 mol % 3-(3,5-Ph 2 -C 6 H 3 )-H 8 -BINOL and aldehydes to provide diarylmethanols with high ee. In a similar vein, Gau and coworkers employed salt-free Ar 3 Al•THF reagents in combination with titanium tetraisopropoxide and either H 8 -BINOL64 or sulfonamide alcohol-based ligands,65 which led to diarylmethanols with high enantioselectivities. These reactions may proceed via an Ar-Ti intermediate 66…”
Section: Introductionmentioning
confidence: 99%
“…However, organoaluminum reagents were used in limited cases of asymmetric catalytic alkylation, allylation, allylic alkylation, and alkynylation reactions, achieving products in good to excellent enantioselectivies. Recently, our group demonstrated that the [AlAr 3 (THF)] reagents are efficient aryl nucleophiles for the additions to aldehydes and ketones catalyzed by titanium catalyst of ( R )-H 8 -BINOL, ( S )-BINOL (BINOL = 2,2′-dihydroxy-1,1′-binaphthyl), or sulfonamide alcohols. Furthermore, [AlAr 3 (THF)] is an effective coupling reagent with aryl halides .…”
mentioning
confidence: 99%